2015
DOI: 10.1021/bi501486z
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein AI Deficiency Inhibits Serum Opacity Factor Activity against Plasma High Density Lipoprotein via a Stabilization Mechanism

Abstract: The reaction of Streptococcal serum opacity factor (SOF) against plasma high-density lipoproteins (HDL) produces a large cholesteryl ester-rich microemulsion (CERM), a smaller neo HDL that is apolipoprotein (apo) AI-poor, and lipid-free apo AI. SOF is active vs. both human and mouse plasma HDL. In vivo injection of SOF into mice reduces plasma cholesterol ~40% in 3 hours while forming the same products observed in vitro, but at different ratios. Previous studies supported the hypothesis that labile apo AI is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It plays important roles in preventing lipid accumulation in tissues and in maintaining cholesterol dynamic balance [ 17 , 18 ]. Genetic deficiency in Apo A-I has been associated with excessive cholesterol accumulation in human and poultry [ 19 21 ]. Association studies showed that a single nucleotide polymorphism (SNP) upstream of the ATG initiation codon of the chicken Apo A-I gene was associated with abdominal fat weight and abdominal fat percentage [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It plays important roles in preventing lipid accumulation in tissues and in maintaining cholesterol dynamic balance [ 17 , 18 ]. Genetic deficiency in Apo A-I has been associated with excessive cholesterol accumulation in human and poultry [ 19 21 ]. Association studies showed that a single nucleotide polymorphism (SNP) upstream of the ATG initiation codon of the chicken Apo A-I gene was associated with abdominal fat weight and abdominal fat percentage [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…[32] The kinetics of the SOF reaction with HDL and acylated HDL were determined by right angle light scattering in real time and according to the distribution of reaction products by SEC as described. [23, 33] Briefly, HDL (0.27 mg/mL in 3 mL) was placed in a fluorescence cuvette, which was transferred to the cell compartment of an Aviv spectrofluorimeter. After equilibration to 37 °C, SOF (2.8 μg/2.5 μL) was added with constant stirring and the light scattering intensity (325 nm) monitored at 90° to the incident light.…”
Section: Methodsmentioning
confidence: 99%
“…The rate-limiting step of the SOF reaction is apo AI desorption from the HDL surface [46]. The SOF reaction mechanism was revealed by chemical kinetic studies of its reaction vs. HDL [2] and by cryo electron microscopy [4]; SOF is a fusogen that binds a “host” HDL with a high affinity binding site and a “guest” HDL with a lower affinity delipidation site.…”
Section: Introductionmentioning
confidence: 99%